Seasonal variations of the ichthyoplankton assemblage in the Yangtze Estuary and its relationship with environmental factors - Hui Zhang; Weiwei Xian; Shude Liu (PeerJ, 2019)
Seasonal variations of the ichthyoplankton assemblage and its relationship with the environment were analyzed based on four seasonal surveys during 2012. Historical data was collected to be compared with results from previous years in order to indicate the seasonal and inter-annual variation of the ichthyoplankton assemblage in the Yangtze Estuary and the adjacent waters. A total of 3,688 individuals belonging to 5 orders, 9 families, and 15 species were collected. No samples were collected in the winter cruise. In 2012, all samples were separated into four ecotypes, which is comparable with the historical data from previous years. The Engraulis japonicus was the most abundant species of all teleost fishes. The E. japonicus was captured in every season and contributed the most to the abundance of ichthyoplankton, which was greater than that of previous years. This result may be due to the periodic fluctuations of E. japonicus or from the displacement of spawning grounds offshore for environmental reasons. The diversity indices of the assemblage were significantly different among seasons, with the number and abundance of the species peaking in the spring, while richness, evenness and diversity indices peaked in the autumn. The species richness of the ichthyoplankton varied from 0.74 to 1.62, the Pielou evenness index varied from 0.10 to 0.49 and the Shannon–Wiener index varied from 0.19 to 1.04. The results of CCA analysis showed that the major factors affecting the ichthyoplankton assemblage differed throughout the seasons. Chla was the key factor affecting the ichthyoplankton in 2012. These seasonal and inter-annual variations likely resulted from migrations associated with fish spawning as well as the environment. Compared with data from previous studies, the relationship between the assemblage structure of ichthyoplankton and corresponding environmental variables have undergone a decline.